Acute toxicity study of Dermabin - V. L. Karbovskyy; I. A. Shevchuk; O. V. Kurkina; T. Ye. Makovska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The problem of improving the therapy of patients with psoriasis and psoriatic arthritis still remains to be one of the most pressing in the up-to-date dermatology, despite a considerable number of the available and newly appeared medications.